RANCANG BANGUN PROTOTIPE LEMARI PENGERING PAKAIAN OTOMATIS BERBASIS IOT (INTERNET OF THINGS) - Iqbal, Muhammad; Tri Desrehan, Sagit; Febriansyah, Aan; Yudhi (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Drying is a process of simultaneous transfer of heat and water vapor that requires heat energy to evaporate the water content contained in the material being dried by a drying medium that is usually heat, at this time the development of modern technology and automation of electronic equipment has changed the way work is done, including clothes dryers. This tool is able to dry various types of clothes such as t-shirts, cotton, jeans, and jackets, which are commonly used daily. The author developed an IoT-based automatic clothes dryer using electrical energy. This tool works with a heating system that comes from a heater that is spread by an AC fan so that it is evenly distributed throughout the closet. And the IoT functions as monitoring conditions in the closets such as temperature, humidity and time, Drying can be done independent of the weather and following a predetermined time and temperature, with an optimal room humidity levels: 75% t-shirt, 74% cotton, 77% jeans, and 77% jacket.